Western and complementary alternative medicine treatment of uremic pruritus: A literature review - Ping-Hsun Lu; Yu-Chih Tai; Min-Chien Yu; I-Hsin Lin; Ko-Lin Kuo (Tzu Chi Medical Journal)
Uremic pruritus (UP), also called chronic kidney disease-associated pruritus (CKD-aP), is a bothersome symptom that causes sleep disturbance, anxiety, depression, and reduced quality of life. Pruritus often occurs in patients with end-stage renal disease. There is still no definite treatment for UP due to its unclear pathogenesis. We searched electronic databases (PubMed and Google Scholar) and gathered the latest clinical trials and pilot studies of Western and complementary alternative medicine (CAM) therapies for UP in English. These UP studies were separated into three main groups: systemic, topical, and others and CAM. Gabapentin, nalfurafine, acupuncture, and Chinese herbal bath therapy (CHBT) show antipruritic effects, with higher evidence grades in the meta-analysis. Emollients with additive compounds are more effective for reducing itch than emollients without additives. Supplements for deficient elements, such as zinc, omega-3, and omega-6, also show benefits for pruritus improvement. CAM therapies such as acupuncture, herbs, and herbal baths or creams all have good results for UP treatment. We summarize the treatments and suggest a treatment algorithm for UP according to severity. Some UP therapies are already supported by large-scale clinical evidence, and some new treatments can provide patients with new hope and treatment options. However, these new methods still need large population studies and further exploration.